Revelação cristã e culturas afro-brasileiras à luz da teologia de Andrés Torres Queiruga - Boaventura, Josuel dos Santos (2012)
Afro-Brazilians descend from cultures profoundly religious, in which God experience guides all existence. They accept divine revelation in their everyday lives and they answer to God that reveals himself in a very creative way. Theologian Andrés Torres Queiruga helps us to reflect upon this happening of divine revelation that takes place in the history and in the innermost of each human being like a creating and saving action. Before the Jewish particularism that closed at their limits all revelation and salvation possibilities, the concrete experience of Jesus of Nazareth reveals that God loves everyone as sons and daughters and He wants all people to be saved. The Second Vatican Council helped us to update this good news, recognizing in all cultures and religions this revelatory and salvific presence of God, challenging all the church to a respectful approach, typical of who wants to listen more than to talk.The encounter with black cultures was initially dramatic, but the rediscovery of the Christian message with a liberating and salvific content, it made possible a compromised engagement of the African descendent contributing dynamically in the evangelization process. The Liturgical-pastoral action, attentive to enculturation demands, seeks to take into account the values of these and other cultures, so that the mystery of Christ be expressed and celebrated fully and fruitfully. Thenceforth at living the essential Christian identity, ours discover that we are called to dialogue with those who profess a faith different from us and like us live in full pursuit of truth, as it is the case of religions of African origin